The Understanding of Graduate Students at Yarmouk University of the Principles of BrainBased Learning and their Attitudes towards them - Malkawi , Amal; Jamal Alkhatib, Sara (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed at evaluating graduate students’ understanding of brain-based learning principles at Yarmouk University and their attitudes towards them. The study targeted two stratified random samples, the size of each was 85 graduate students of the Department of Curricula and Teaching Methods at the Faculty of Education, Yarmouk University, Jordan. Two pilot-structured tools, a test and a scale, were built to evaluate, respectively, the understanding of BBLP and the attitudes towards them. The results showed an intermediate mean level of understanding of BBLP among the whole study sample. In addition, the levels of understanding of BBLP were found to be significantly associated (α < 0.05) with the program level and with the field of specialization, with higher levels of understanding being found among PhD students and students of science curricula and teaching methods compared to master’s students and students of other fields of specialization, respectively. With regards to the attitudes towards BBLP among the students, the results revealed a high mean level of attitude among the whole sample towards BBLP. Similar to their effects on the students’ understanding of BBLP, the program level and the field of specialization were both found to be significantly associated (α < 0.05) with the attitudes towards BBLP; PhD students and students of science curricula and teaching methods showed higher trending towards BBLP compared to their counterparts. In view of the above, the study recommends paying more attention to the theory of BBLP through conducting further research by graduate students on how to reap benefits from the theory in teaching and learning, and it encourages the teaching staff at the Faculty of Education to give more attention to the teaching of BBLP to the students of the faculty.